(untitled) (Shanti Journal, 2023)
The representation of the body in new media appears to be focused on navigating gendered norms of the body image, particularly those of masculinity and femininity, and perceived ideals of beauty as a sign of sexual attraction. The goal of this study is to examine how social networks contribute to the development of stereotypes that rely on body visibility. TikTok is one of the most current social networking applications (SNAs) that allow users to create, modify, and share short form films. The research technique offers a self-representation focused content analysis of sample videos. Such analysis examines the impact SNAs have on the formation and expression of users’ notions of beauty and gender through their digital representations of the body.